2000
DOI: 10.3354/dao039211
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteriosis in wild rabbitfish Siganus rivulatus associated with cage farming in the Gulf of Eilat, Red Sea

Abstract: Infection patterns of Mycobacterium rnarinum were studied over a period of 3 yr in wild rabbitfish Siganus rivulatus populations associated with commercial mariculture cages and inhabiting various sites along the Israeli Red Sea coastline. Mycobacteriosis was first recorded from the Red Sea in 1990 in farmed sea bass Dicentrarchus labrax and is absent from records of studies on parasites and diseases of wild rabbitfish carned out in the 1970s and 1980s. A sharp increase in the prevalence of the dsease in cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
2
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 21 publications
2
45
2
4
Order By: Relevance
“…1). The Israeli marine strain was first isolated from cultured sea bass (Dicentrarchus labrax), but many Red Sea species appear to be susceptible to infection (5,8,33).Newly emerging mycobacterial fish pathogens from the Chesapeake Bay in the United States have also been reported (15,25). In 2005 a new mycobacterial species, Mycobacterium pseudoshottsii, was described in association with epizootic fish disease among striped bass (Morone saxatilis) in the Chesapeake Bay, Maryland.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1). The Israeli marine strain was first isolated from cultured sea bass (Dicentrarchus labrax), but many Red Sea species appear to be susceptible to infection (5,8,33).Newly emerging mycobacterial fish pathogens from the Chesapeake Bay in the United States have also been reported (15,25). In 2005 a new mycobacterial species, Mycobacterium pseudoshottsii, was described in association with epizootic fish disease among striped bass (Morone saxatilis) in the Chesapeake Bay, Maryland.…”
mentioning
confidence: 99%
“…1). The Israeli marine strain was first isolated from cultured sea bass (Dicentrarchus labrax), but many Red Sea species appear to be susceptible to infection (5,8,33).…”
mentioning
confidence: 99%
“…Προσβάλλονται πάνω από 150 είδη ψαριών, στα οποία προκαλείται χρόνια νόσος που παραμένει ασυμπτωματική για μεγάλο διάστημα (Toranzo et al 2005). Είδη του γένουςMycobacterium μπορούν να ε πιζήσουν μέσα στο νερό και στον πυθμένα της θά λασσας έως και 2 χρόνια (Reichenbach-Klinke 1972), ενώ η μετάδοση τους με το νερό έχει δειχθεί σε επι δημιολογικές μελέτες (Diamant et al 2000;Korun et al 2005).…”
Section: παθογόνα βακτηρίδια που προσβάλλουν τα ευρύαλα ψάρια της μεσunclassified
“…Observations and field data collected over the years indicate an increase in breakage of reef-building coral branches, decline in coral species diversity and recruitment rates and overall number of live coral colonies in Eilat's nature reserve (Zakai and Chadwick-Furman 2002). There is an increased incidence of diseased coral (Sussman et al 2003) and fish, shown to be linked with anthropogenic activity (Diamant et al 2000;Diamant 2001;Colorni et al 2002).…”
Section: The Red Seamentioning
confidence: 99%